A comparative analysis of linguistic components depicting individual preparedness, health problems and communal wellbeing in Misery and Thank You M'am - Mojgan Eyvazi (Shahid Beheshti University of Medical Sciences, 2023)
Background: One of the main goals of health organizations is to prepare all members to solve their needs and problems so that all people can integrate with each other and with the whole society. The purpose of this study was to defend the idea of how these two writers give priority to collective values and not to the personal interests of the characters, which can be a threat to the concept of well-being and health, through the analysis of Anton Chekhov's "Misfortune" and Langston Hughes' "Thank You Ma'am". Methods: This research is a quantitative study of language patterns in both stories with a parallel examination of different realizations and representations of preparation, individualism and well-being, which has examined the linguistic elements of the strategies presented by Anton with a detailed statistical analysis. Chekhov and Langston Hughes direct all action and dialogue between relatively distant cultural identities in order to foster some collective value, and thus individual well-being and promoting health. Results: The average length of expression in morphemes (MLUm) and the average length of expression in words (MLUw) were almost completely correlated. This finding shows that MLUw can be used as effectively as the mothers as a measure of the child's gross language development, which can be a decisive and important policy in health sector communication. Conclusion: The classification of the introduced words/phrases was useful in comparing other literary texts and also to examine the different styles that the authors may use in the speech of their writings.